2015
DOI: 10.1128/iai.00230-15
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Reprogramming by Plasmid-Encoded Transcriptional Regulators Is Required for Host Niche Adaption of a Macrophage Pathogen

Abstract: bRhodococcus equi is a facultative intracellular pathogen of macrophages, relying on the presence of a conjugative virulence plasmid harboring a 21-kb pathogenicity island (PAI) for growth in host macrophages. The PAI encodes a family of 6 virulence-associated proteins (Vaps) in addition to 20 other proteins. The contribution of these to virulence has remained unclear. We show that the presence of only 3 virulence plasmid genes (of 73 in total) is required and sufficient for intracellular growth. These include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 42 publications
1
53
0
1
Order By: Relevance
“…Additional factors encoded by the virulence plasmid (Coulson et al, 2015) are likely needed to boost VapA production by intracellular rhodococci and VapA may have activities beyond those presented here. Neutralisation of lysosome and phagosome pH increases bacterial viability and allows virulent, that is VapA-producing R. equi, to utilise intraphagosomal contents as a source of nutrients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additional factors encoded by the virulence plasmid (Coulson et al, 2015) are likely needed to boost VapA production by intracellular rhodococci and VapA may have activities beyond those presented here. Neutralisation of lysosome and phagosome pH increases bacterial viability and allows virulent, that is VapA-producing R. equi, to utilise intraphagosomal contents as a source of nutrients.…”
Section: Discussionmentioning
confidence: 93%
“…This explains why rVapA can turn a plasmid-less, avirulent R. equi isolate into a pathogen for macrophages. Additional factors encoded by the virulence plasmid (Coulson et al, 2015) are likely needed to boost VapA production by intracellular rhodococci and VapA may have activities beyond those presented here. To our knowledge, this is the first example of a Gram-positive pathogen whose membraneactive protein produced in one compartment is transferred to another compartment where it increases membrane permeability.…”
Section: Discussionmentioning
confidence: 93%
“…the expression of ϳ18% of chromosomal genes, impacting the cell's regulatory network to permit adaption to the macrophage environment (32). It is of relevance to note that all strains of each isogenic set carry the virulence plasmid, and the interactions between the virulence plasmid and chromosomal regulation might contribute to differences observed in in vitro growth of macrolide-resistant R. equi isolates in BHI compared to MM.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant aspect of plasmid biology that has hitherto been studied in less detail corresponds to the crosstalk that the resident plasmid establishes with the host regulatory networks (Coulson et al ., ; Yun et al ., ). In this context, we have shown that plasmid R27 significantly influences Salmonella transcriptome, but especially when cells grow at low temperature (25°C) and enter the stationary phase (Paytubi et al ., ).…”
Section: Introductionmentioning
confidence: 99%